PRESENCE OF hemA-LIKE AND hemT-LlKE GENES IN A JSUMBER OF ANOXYGENIC PHOTOSYNTHETIC BACTERIAL ISOLATES FROM INDONESIA AND SOIL SAMPLES FROM BOGOR AREA - AINI, NURUL; SUWANTO, ANTONIUS (BIOTROPIA, 2024)
The Rhodobacter sphaeroides hemA and hemT are known to encode a distinct 5-aminolevulinic acid (ALA)-synthase isozyme. This enzyme catalyzes the first and rate limiting step in ALA biosynthesis through the C4 pathway. This study was carried out to detect hemA-\\ke and hemT-\\ke genes in twenty Anoxygenic Photosynthetic Bacterial (APB) isolates from several wetland areas in Indonesia, and four DNA samples that were isolated from four soil samples obtained from Bogor area. Hybridization techniques of Southern and dot blot were used, using hemA and hemT fragment as probes. Southern hybridization analyses indicated the presence of hemA-\\ke gene in five of APB isolates, i.e., MB15, MB16, MB21.2, MB55 and MB6, whereas hemT-\\ke gene was detected only in MB15. Dot blot hybridization analyses suggested that the soil samples from waterlogged paddy-field, dry paddy-field as well as a mud pond were predominantly occupied by prokaryotic organisms which harboured hemA-]\ke gene. However, /iem7"-like sequences were also found in soil sample from dry paddy-field. Key words: hemA-\\ks gene / hemT-\\ke gene / Southern hybridization analysis / dot blot hybridization analysis.